2014
DOI: 10.1063/1.4867977
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-concentration effect on p-type CuAlOx resistive switching behaviors and the nature of conducting filaments

Abstract: Resistive-switching (RS) memories with good performance and flexibility are demonstrated in p-type amorphous CuAlOx. The nature of conducting filaments (CFs) is studied via the dependence of RS behaviors on the oxygen concentration of CuAlOx. It is observed that with increasing oxygen concentration, (1) both resistance-states and switching-voltages reduce, showing an opposite trend to popular n-type oxide devices; and (2) a transition from non-degenerate to degenerate states occurs in CFs. These observations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
0
26
1
Order By: Relevance
“…This is probably because the number of available p‐type oxides is less and the resistive memory mechanism in p‐type oxides has not yet been clearly revealed. However, few p‐type oxide materials such as NiO x , CuO x , Co 2 O 3 , CuAlO x have been reported so far for resistive switching applications. We have recently reported the resistive switching memory performance in another p‐type oxide, SnO .…”
Section: Introductionmentioning
confidence: 99%
“…This is probably because the number of available p‐type oxides is less and the resistive memory mechanism in p‐type oxides has not yet been clearly revealed. However, few p‐type oxide materials such as NiO x , CuO x , Co 2 O 3 , CuAlO x have been reported so far for resistive switching applications. We have recently reported the resistive switching memory performance in another p‐type oxide, SnO .…”
Section: Introductionmentioning
confidence: 99%
“…However, few reports on CuAlO x RRAMs are found. Zhang et al [11] demonstrated high-performance, flexible RRAM prototype devices using amorphous p-type CuAlO x with different oxygen concentrations as the switching layer. For Cu:AlO x /TaO x /TiN memory devices, memory characteristics and switching mechanism were investigated by Roy et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the p-type and n-type semiconductor materials have the opposite oxygen concentration dependence. Based on the redox, some opposing resistive switching behaviors usually are observed in p-type and n-type oxides, such as the bias polarity dependence and the forming location of the conductive filaments [ 10 , 11 , 12 ]. This may be attributed to the different conductive nature for p-type semiconductor (cation vacancy) and n-type semiconductor (oxygen vacancy) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%